Highly oriented graphene growth and characterization - Saheed, M.S.M. (American Institute of Physics Inc., 2016)
Combination of the highly ordered monolayers to form the multilayer interconnected graphene is essential to produce robust and free standing graphene unlike its counterpart 2D monolayers. Here, chemical vapor deposition (CVD) technique is employed to produce highly flexible and high mobility 3D graphene. In this study, the 3D graphene is grown via direct carbon deposition on sacrificial template. With the use of polymer coating such as poly methyl methacrylate (PMMA), it is observed that the graphene is bendable without any degradation. Great potential in term of electrical conductivity and flexibility can be exploited for future work for this CVD grown 3D graphene. Â© 2016 Author(s).